A New Species of Vollenhovia (Hymenoptera, Formicidae) From India with Key to Known Indian Species - Bharti, H.; Kumar, R. (Вестник зоологии, 2013)
Vollenhovia gastropunctata Bharti et Kumar, sp. n. (Hymenoptera, Formicidae) is described and illustrated based on the worker caste from India. A key to the Indian species of Vollenhovia Mayr, 1865 is provided.